2006
DOI: 10.1007/s11199-006-9028-9
|View full text |Cite
|
Sign up to set email alerts
|

Personal Control, Self-Efficacy in Sexual Negotiation, and Contraceptive Risk among Adolescents: The Role of Gender

Abstract: Adolescents' sexual decision making is shaped by normative ideas about Bappropriate^sexual roles for women and men; consequently, the motivation and ability to engage in safer sex may be different for adolescent girls and boys. The aim of this study was to explore how social-psychological resources influence the behavior of girls and boys within the highly gendered and inequitable domain of sexual relationships. I used data from the National Longitudinal Study of Adolescent Health (Add Health) to examine wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
65
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 38 publications
6
65
1
2
Order By: Relevance
“…Sayles et al (2006), menyatakan bahwa remaja yang telah berbicara atau konseling dengan orang lain, selain orang tua atau wali, tentang HIV/AIDS dan yang memiliki tujuan hidup, dilaporkan memiliki pengetahuan tentang cara menghindari infeksi HIV dan cenderung lebih memiliki self efficacy yang tinggi. Hasil penelitian Pearson (2006), menunjukkan bahwa kontrol pribadi dan self-efficacy dalam negosiasi seksual dengan pasangan, secara signifikan berhubungan dengan perilaku seks yang lebih aman, dan seringkali lebih penting untuk anak perempuan daripada anak lakilaki dalam memprediksi risiko perilaku aman menggunakan kontrasepsi. Dillon et al (2008), menyatakan bahwa konseling (LGBAfirmatif) berdampak pada peningkatan self efficacy dan berhubungan positif dengan definisi jenis kelamin dirinya.…”
unclassified
“…Sayles et al (2006), menyatakan bahwa remaja yang telah berbicara atau konseling dengan orang lain, selain orang tua atau wali, tentang HIV/AIDS dan yang memiliki tujuan hidup, dilaporkan memiliki pengetahuan tentang cara menghindari infeksi HIV dan cenderung lebih memiliki self efficacy yang tinggi. Hasil penelitian Pearson (2006), menunjukkan bahwa kontrol pribadi dan self-efficacy dalam negosiasi seksual dengan pasangan, secara signifikan berhubungan dengan perilaku seks yang lebih aman, dan seringkali lebih penting untuk anak perempuan daripada anak lakilaki dalam memprediksi risiko perilaku aman menggunakan kontrasepsi. Dillon et al (2008), menyatakan bahwa konseling (LGBAfirmatif) berdampak pada peningkatan self efficacy dan berhubungan positif dengan definisi jenis kelamin dirinya.…”
unclassified
“…A sense of sexual autonomy helps youth to navigate sexual interactions: Teens who have a greater sense of control in sexual situations are more likely to refrain from intercourse and use condoms when they have sex (Pearson, 2006). When girls report more sexual subjectivitydbody esteem, entitlement to pleasure, and sexual self-reflectiondthey experience greater self-efficacy in condom use (Horne & Zimmer-Gembeck, 2006).…”
mentioning
confidence: 99%
“…It has been reported that gender power distributions manifest in sexual situations (Blanc, 2001;Dodoo & Tempenis, 2002;Pearson, 2006). For example, in cultures where women are expected to be docile and less expressive of their needs, this behavior extends to the sexual act and can cause women to engage in risky sexual behaviors without speaking up for themselves (Lucke, 1998;Pearson, 2006;Varga, 2003). However, this literature was not fully supported in the current study.…”
Section: Samplecontrasting
confidence: 61%
“…These expectations have been found to influence the way that adolescent females deal with members of the opposite sex, especially in sexual situations (Blanc, 2001;Browning, Hatfield, Kessler, & Levine, 2000;Dodoo & Tempenis, 2002;Gage, 1998;Lucke, 1998;Pearson, 2006;Varga, 2003). It has been reported that gender power distributions manifest in sexual situations (Blanc, 2001;Dodoo & Tempenis, 2002;Pearson, 2006). For example, in cultures where women are expected to be docile and less expressive of their needs, this behavior extends to the sexual act and can cause women to engage in risky sexual behaviors without speaking up for themselves (Lucke, 1998;Pearson, 2006;Varga, 2003).…”
Section: Samplementioning
confidence: 99%